2019
DOI: 10.1039/c9sc02923k
|View full text |Cite
|
Sign up to set email alerts
|

Ion-pair induced supramolecular assembly formation for selective extraction and sensing of potassium sulfate

Abstract: The formation of a supramolecular core–shell like assembly upon interaction of the receptor with potassium sulfate enables its selective extraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 41 publications
2
50
0
Order By: Relevance
“…31 More recently, Romanski and coworkers have demonstrated that a ditopic receptor extracts potassium sulfate from aqueous solution. 33 In related work, the transport of sulfate across a bilayer membrane has been shown to be facilitated by tripodal thioureas. 17 However, receptors that can transport sulfate across a bulk liquid membrane to facilitate receptor recycling for realworld applications of sulfate extraction remain unexplored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 More recently, Romanski and coworkers have demonstrated that a ditopic receptor extracts potassium sulfate from aqueous solution. 33 In related work, the transport of sulfate across a bilayer membrane has been shown to be facilitated by tripodal thioureas. 17 However, receptors that can transport sulfate across a bulk liquid membrane to facilitate receptor recycling for realworld applications of sulfate extraction remain unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…11 While a number of receptors for selective sulfate recognition have recently been reported, [13][14][15][16][17][18][19][20][21][22][23][24][25] there are relatively few examples of suitable receptors that overcome the Hofmeister bias to allow LLE of sulfate. [26][27][28][29][30][31][32][33] Sessler and co-workers have successfully employed calix[n]pyrroles to extract sulfate into organic media in the presence of methyltrialkylammonium ions. [26][27][28] Wu and co-workers have demonstrated that a tripodal hexaurea receptor is capable of extraction of sulfate ions into chloroform solution in the presence of TBACl and that the sulfate can be back-extracted with aqueous barium chloride to regenerate the receptor as a chloride complex.…”
Section: Introductionmentioning
confidence: 99%
“…OxP-1N18C6 gives selective color variations, see Figure S1) due to deproto-nation under the conditions indicated while OxP-1N12C4 is essentially unresponsive( Figure S1) and has been included asa controlc ompound. Notably,t hese color variations represent the potential for detection of ammonium,n itrate, phosphate and carbonate species in the presence of naturally occurring sodium,p otassium, chloride and sulphatei ons [30] although the main purpose here is chromogenic detection of ammonium nitrate. Electronic absorption spectra in the presence of different salts in the aqueous phase are shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…7,[11][12][13] Examples of applied supramolecular innovation include the development of medical diagnostic sensors, enabled through advances in selective host-guest complex formation; 7,14 maintenance free materials, created through incorporation of reversible non-covalent moieties within material constructs; 15,16 and ion extraction realised through the development of molecular encapsulation technologies. 17,18 Herein, we update and expand on a previous review by Kolesnichnko and Anslyn, 19 to discuss the application of supramolecular chemistry in the real world.…”
Section: Introductionmentioning
confidence: 95%